The Influence of Local Government Spending and Village Funds on Inclusive Economic Development in Indonesia - Purwanti, Dyah; Nurhidayati, Nurhidayati (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2025)
Research originality — This study is the first to analyze how government fiscal instruments, specifically the local government spending, have a different role in pillars of inclusive economic development. In addition, the study examines whether village funds, which are the lowest-level of fiscal instrument, play a strategic role in creating inclusivity in regional economic development. It provides a synthesis of knowledge on the role of government fiscal policy in promoting inclusive economic development. Research objectives — This study provides an overview of the empirical findings on how local government spendings and village funds affect the realization of inclusive economic development. Research methods — The study utilized data from the inclusive economic development index (inclusive index), regional spending based on economic, education, and health functions, and village funds at the provincial level from 2015 to 2021. The study used panel data with multivariate regression analysis. Empirical results — The study found that expenditure for education and road strengthened the inclusive index. Economic and health expenditures showed a partial impact on inclusive economic development. Economic expenditure was found to strengthen the economic growth pillar, but it reduced the equity and poverty pillar. The finding underlines that economic expenditure seems to be pro-growth, but not pro-poor. Another finding is that the village funds supported the pillar of equity and poverty. Implications — The implication of this study is the improvement of the quality of government spending, especially educational expenditure, which has been proven to have a significant impact on the inclusive index. Another implication is the possibility that the quality of economic expenditure is improved because it is not fully pro-poor.